2007
DOI: 10.1084/jem.20070719
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid mediates enhanced T reg cell growth, differentiation, and gut homing in the face of high levels of co-stimulation

Abstract: We demonstrate that all-trans retinoic acid (RA) induces FoxP3+ adaptive T regulatory cells (A-Tregs) to acquire a gut-homing phenotype (α4β7+ CC chemokine receptor 9+) and the capacity to home to the lamina propria of the small intestine. Under conditions that favor the differentiation of A-Tregs (transforming growth factor–β1 and interleukin 2) in vitro, the inclusion of RA induces nearly all activated CD4+ T cells to express FoxP3 and greatly increases the accumulation of these cells. In the absence of RA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
672
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(721 citation statements)
references
References 28 publications
(39 reference statements)
32
672
2
5
Order By: Relevance
“…Less than 15% of the iTreg had reverted in vivo 8 and 14 days after transfer into untreated syngeneic mice (Fig. 2E) confirming previously published results [14,19]. In contrast, Foxp3 expression of the transferred iTreg was not stable after transfer to irradiated hosts (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Less than 15% of the iTreg had reverted in vivo 8 and 14 days after transfer into untreated syngeneic mice (Fig. 2E) confirming previously published results [14,19]. In contrast, Foxp3 expression of the transferred iTreg was not stable after transfer to irradiated hosts (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The co-culture of purified Foxp3 À CD4 1 T cells with CD-DC under conditions supporting the generation of iTreg, i.e. with TGF-b [10, 11], IL-2 [12] and retinoic acid (RA) [13,14], induced expression of Foxp3 in approximately $12% of CD4 1 T cells (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of surface expression of galectin-3 is particularly interesting given the recent observation that galectin-3, recruited intracellularly to the immunological synapse, negatively regulates TCR-mediated CD4 1 T-cell activation [28]. Generation of Treg has been associated with suboptimal T-cell activation, resulting from antigen presentation by immature or sub-optimally primed DC [29,30]. The ability of galectin-3 to influence the immunological synapse together with the ability of SEA to modulate DC maturation may play a key role in favoring the development of Foxp3-expressing cells in our T-cell/DC co-cultures [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary components likely also influence the development of the mucosal immune system in many ways, including stabilization of the microbiota. RA, a metabolite of dietary component vitamin A, has been shown to educate the mucosal DC to imprint primed T cells and B cells with gut tropism [21][22][23][24]. Recent reports further demonstrated that intestine is enriched for DC expressing RA metabolizing enzyme ALDH1a and that RA is a key regulator of TGF-b dependent immune responses by promoting Treg differentiation and inhibiting Th17 cell development [9,11].…”
Section: Introductionmentioning
confidence: 99%